Epidural extension failure in obese women is comparable to that of non‐obese women. Issue 6 (4th February 2018) - Eley, V. A.; Chin, A.; Tham, I.; Poh, J.; Aujla, P.; Glasgow, E.; Brown, H.; Steele, K.; Webb, L.; van Zundert, A.
Abstract : Background: Management of labor epidurals in obese women is difficult and extension to surgical anesthesia is not always successful. Our previous retrospective pilot study found epidural extension was more likely to fail in obese women. This study used a prospective cohort to compare the failure rate of epidural extension in obese and non‐obese women and to identify risk factors for extension failure. Methods: One hundred obese participants (Group O, body mass index ≥ 40 kg/m 2 ) were prospectively identified and allocated two sequential controls (Group C, body mass index ≤ 30 kg/m 2 ). All subjects utilized epidural labor analgesia and subsequently required anesthesia for cesarean section. The primary outcome measure was failure of the labor epidural to be used as the primary anesthetic technique. Risk factors for extension failure were identified using Chi‐squared and logistic regression. Results: The odds ratio (OR) of extension failure was 1.69 in Group O (20% vs. 13%; 95% CI: 0.88–3.21, P = 0.11). Risk factors for failure in obese women included ineffective labor analgesia requiring anesthesiologist intervention, (OR 3.94, 95% CI: 1.16–13.45, P = 0.028) and BMI > 50 kg/m 2 (OR 3.42, 95% CI: 1.07–10.96, P = 0.038). Conclusion: The failure rate of epidural extension did not differ significantly between the groups. Further research is needed to determine the influence of body mass index > 50 kg/m 2 on epidural extension for cesarean section.